DEVELOPING ALGORITHMIC THINKING IN ELEMENTARY SCHOOL STUDENTS USING LEGO WEDO - Anuarbekova, Г.Ж.; Tekesbaeva, Н.А.; Smagul, Б.Қ.; Moshkalov, А.Қ.; Bedelov, Қ.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
Abstract This study is devoted to the study of the effectiveness of using the LEGO WeDo Education constructor for the development of algorithmic thinking in younger schoolchildren. The purpose of the work is to develop and test a methodology for teaching the basics of algorithmization based on interactive LEGO WeDo models. The objectives of the study included studying the impact of practice-oriented classes on the formation of logical thinking and consistent planning skills, as well as evaluating the effectiveness of using a construction kit in the educational process. The methodology included experimental training with the participation of students in grades 2-4, questionnaires and analysis of the results of the tasks. During the experimental work, a special training program was developed, including the construction and programming of LEGO models. The results of the study showed that systematic classes with LEGO WeDo contribute to a significant increase in the level of algorithmic thinking among students, manifested in improving the ability to analyze tasks, develop a sequence of actions and evaluate results. The data obtained confirm the prospects of using LEGO WeDo in the educational process for the formation of important competencies needed in the modern world